TLR5 Polymorphisms rs2072493, rs5744174, and rs5744168 Are Not Genetic Risk Factors for Chronic Helicobacter pylori Infection in Indian Tamils. (18th August 2017) - Goda, Vaishnavi; Jayaraman, Megala; Loganathan, Rekha; Nazeer, Mehnaz; Ali, Mohammed; Karunakaran, Premkumar; Devaraju, Panneer
ABSTRACT: The incidence of Helicobacter pylori ( H. pylori ) infection and gastric cancer is on the rise in India, and the genetic factors influencing the increased susceptibility in Indian population remain obscure. Toll-like receptors (TLRs) play a major role in innate immune system and genetic polymorphisms affecting their function were reported to enhance the risk for H. pylori infection. Seventy-seven patients ( n = 77) diagnosed with H. pylori infection and 230 healthy subjects were recruited in this study. The rs2072493, rs5744174, and rs5744168 polymorphisms within TLR5 gene were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and Tetra-ARMS PCR genotyping techniques. Present study revealed that these studied polymorphisms are less frequent in south Indian Tamils and thus failed to confer a significant risk to develop chronic H. pylori infections. The distribution of ancestral allele of rs2072493 polymorphism conferred resistance to develop chronic H. pylori infection in our population ( p = 0.024; OR = 0.53; 95% CI: 0.3–0.91). The lesser incidence of polymorphic alleles suggests that the TLR5 gene is under genetic selection pressure to withstand the prevailing endemic infections among south Indian Tamils.